Loyola University New Orleans College of Law : A History - Medina, M. Isabel (Book collections on Project MUSE., 2016)
"This chronicle of Loyola University New Orleans College of Law examines the prominent Jesuit institution across its hundred-year history, from its founding in 1914 through the first decade of the twenty-first century. With a mission to make the legal profession attainable to Catholics, and other working-class persons, Loyola's law school endured the hardships of two world wars, the Great Depression, the tumult of the civil rights era, and the aftermath of Hurricane Katrina to emerge as a leader in legal education in the state. Exploring the history of the college within a larger examination of the legal profession in New Orleans and throughout Louisiana, Medina provides details on Loyola's practical and egalitarian approach to education. As a result of the school's principled focus, Loyola was the first law school in the state to offer a law school clinic, develop a comprehensive program of legal-skills training, and to voluntarily integrate African Americans into the student body. The transformative milestones of Loyola University New Orleans College of Law parallel pivotal points in the history of the Crescent City, demonstrating how local culture and environment can contribute to the longevity of an academic institution and making Loyola University New Orleans College of Law a valuable contribution to the study of legal education."--Publisher's website.